Ketamine: a review of its pharmacologic properties and use in ambulatory anesthesia. - Haas, D. A. (American Dental Society of Anesthesiology, 1992)
The administration of intravenous agents is the most commonly used method in Canada and the United States to produce sedation or general anesthesia for dental procedures. Ketamine, a dissociative anesthetic, has several advantageous physical, pharmacokinetic, and pharmacodynamic properties. It can be used to induce anesthesia, sedation, analgesia, and amnesia. Ketamine can maintain functional residual capacity, induce bronchodilation, and avoid cardiovascular depression. However, adverse effects have been demonstrated, such as cardiovascular stimulation and unpleasant emergence phenomena, both of which may be modulated by supplementation with benzodiazepines. An increase in the use of ketamine for ambulatory anesthesia has recently been advocated. This review of the literature supports the use of ketamine as an effective agent for selected anesthetic procedures.